Effects of Cage and Floor Housing Systems on Fattening Performance, Oxidative Stress and Carcass Defects in Broiler Chicken - Simsek, Ulku Gulcihan; Erisir, Mine; Ciftci, Mehmet; Tatli Seven, Pinar (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
This study was carried out to compare floor with cage housing systems used for broiler chicken production in terms of performance, some oxidative stress parameters and carcass defects. For this purpose, two cage and two floor housing farms were monitored simultaneously during summer, autumn and winter seasons. Capacities of farms in each housing system were 40.000 and 25.000 chickens. At the end of each summer, autumn and winter season, 15 broilers were selected in both housing systems with capacity of 25.000 chickens for carcass and oxidative stress parameters. Blood samples were taken in slaughtering period from chickens slaughtered with decapitation. Broiler reared in cage housing showed higher live weight at 7 and 14 days (P <= 0.05). But this difference disappeared after three weeks, while slaughter weights were found to be similar at both systems. Better feed conversion ratio (FCR) and carcass yield were obtained in floor housing (P <= 0.01). Serum malondialdehyde (MDA) level increased in cage housing (P <= 0.01). Other carcass traits and antioxidant activity were found to be similar between groups (P>0.05). Cases of wing fractures, wing and breast bruising were found to be higher in cage housing (P <= 0.05). Case of shank and drumstick bruising slightly increased in floor housing (P=0.074). The incidence and severity of food pad lesions increased in floor housing (P <= 0.01). The results of this study indicated that floor housing had shown better performance and carcass quality at examined production capacities.
Kafes ve yer sistemlerinin etlik piliç üretiminde besi performansi{dotless}, oksidatif stres ve karkas kusurlari{dotless} üzerine etkileri
Keywords: Broiler; Floor housing; Cage housing; Performance; Season